Biological and mechanical degradation affecting the surface properties of aesthetic restorative - Bianca Medeiros Maran; Fabiana Scarparo Naufel; Andréia Bolzan de Paula; Giovana Spagnolo Albamonte Araújo; Regina Maria Puppin-Rontani (Universidade Estadual de Campinas, 2017)
Aim: To evaluate the roughness (Ra), Knoop hardness (KHN) and change of color (∆E) of esthetic restorative materials (Filtek Z350-composite nanoparticle; Empress Direct-composite nanohybrid and IPS e.Max-ceramic) subjected to contact with the Streptococcus mutans biofilm (biological degradation) associated with abrasion generated by tooth brushing (mechanical degradation). Methods: Ten specimens of each material were prepared, and the surface properties initial were evaluated. All specimens were exposed to Streptococcus mutans inoculum; after 7 days, surface properties were evaluated.  The specimens were submitted to a 30,000 toothbrushing cycles, using a toothpaste slurry, then, surface properties were evaluated again. Data were analyzed by Proc-Mixed, One-way ANOVA, Tukey-Kramer and Tukey's tests (α = 0.05). Results: At the baseline, ceramic showed the highest Ra and KHN values; after the biological degradation the composites showed increased Ra, but KHN did not change; after the mechanical degradation, Empress showed decreased Ra and Z350 showed similar Ra, the KHN increased to both composites, and all materials had increased lightness after the mechanical degradation. Conclusions: The results suggest that, when exposed to Streptococcus mutans biofilm and toothbrush abrasion, the ceramics undergoes minimal degradation and the composites exhibited variable degradation, depending on the composition of the material.